Pathways between childhood trauma, clinical symptoms, and functioning in new-onset psychosis: novel insights from a network analysis approach - Dimitrios Kiakos; Luis Alameda; Ines Lepreux; Caroline Conchon; Livia Alerci; Marianna Gorgellino; Nadir Mebdouhi; Teya Petrova; Philippe Golay; Lilith Abrahamyan Empson; Philippe Conus; Sandra Vieira (Schizophrenia)
Abstract Childhood trauma (CT) has been linked to various domains of outcomes in individuals with new-onset psychosis, but the intricate relationships between different types of trauma, clinical symptoms, and functioning remain poorly understood. The aim of this study was to identify patterns of relationships between these three domains in first-episode psychosis (FEP). The study sample consisted of 277 patients from the Treatment and Early Intervention in Psychosis Program (TIPP) at Lausanne University Hospital. Symptom severity was assessed using the Positive and Negative Syndrome Scale (PANSS), functioning was evaluated with an adapted version of the general subscale of the Premorbid Adjustment Scale (PAS), and the five most common CT experiences (sexual, physical and emotional abuse; physical and emotional neglect) was measured using a tailored questionnaire. Data from early assessments (2 and 6 months after admission) were used for analysis. A network model was fitted to estimate the shortest pathways linking different types of CT to various domains of functioning. Our findings revealed two distinct pathways connecting CT to functioning. One pathway influenced occupational functioning through sexual abuse and depression, while another pathway affected socio-personal functioning through physical neglect and stereotyped thinking. Our results suggest that distinct disease phenotypes could be differentially associated with CT and functioning in individuals with new-onset psychosis. This study contributes to the growing evidence supporting the existence of multiple distinct pathways to psychosis, each linked to a different clinical phenotype.